Escaping from Mass Education – Why Harvard Pays - Andreas Bergh; Günther Fink (Lund University, School of Economics and Management, Department of Economics, 2005)
Private universities, as opposed to publicly financed ones, are dominant in some countries and almost non-existent in others. We develop a dynamic model to demonstrate that private providers emerge as soon as they can profitably sell an elite signal to the most highly talented. As private providers engage in cream skimming, the returns to publicly provided education decreases, but the average return to higher education increases because of the signaling benefit created. We use numerical simulations to demonstrate the dynamic implications of our model, and provide some basic empirical evidence in support of the theory presented
Keywords: H52; I22; 330; Higher education; tertiary education; Signaling